(untitled) (International Conference on Computers in Education, 2016)
Many countries around the world have recognized the importance of early childhood education. As facilitators of learning, preschool teachers are expected to plan and provide for their children’s learning by using a variety of resources, including information communication technology (ICT). The term IT refers to digital media or tools, including computers, tablets, multi-touch screens, Internet, digital cameras, audio recorders, and e-book readers. The key purpose of this study is to identify the key ICT competencies that are expected of pre-school teachers. In addition, this study examines the benefits of using ICT with preschool children as perceived by teachers, principals, and parents. This study also identifies the concerns or limitations of using ICT with preschool children.